Mediating Role of Advertising Finance in Crowdfunding Success Factors for MSMEs in Indonesia : Crowdfunding Success Factors - Firmansyah Arifin; Dimas Pratama Putra (Asian Journal of Management, Entrepreneurship and Social Science, 2024)
This study aims to explore the impact of financial literacy, funding objectives, and financial advertising content on crowdfunding success, using 115 crowdfunding platforms registered with the Indonesian OJK as a sample. The study employs signaling theory, particularly in the context of equity crowdfunding platforms, where these platforms serve as signals of business quality for small investors, reducing information asymmetry and encouraging investments. The research methodology employed is descriptive quantitative, using logistic regression analysis to test the hypothesis. The study focuses on companies seeking funding through 10 crowdfunding platforms registered with the Indonesian OJK during the year 2023. Secondary data from published crowdfunding platform records are used, and the sample is determined using purposive sampling techniques. The conceptual framework suggests that financial literacy, funding objectives, and financial advertising content act as partial mediators for crowdfunding success, providing valuable information to both project owners and investors to aid in decision-making processes.